2019
DOI: 10.3390/su11215979
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Multi-Scale Atmospheric Circulation on Severe Haze Events in Autumn and Winter in Shanghai, China

Abstract: Severe haze events have many adverse effects on agricultural production and human activity. Haze events are often associated with specific patterns of atmospheric circulation. Therefore, studying the relationship between atmospheric circulation and haze is particularly important for early warning and forecasting of urban haze events. In order to study the relationship between multi-scale atmospheric circulation and severe haze events in autumn and winter in Shanghai, China, we used a T-mode objective classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Studies have shown there is a correlation between elevated PM 2.5 pollution and decreasing boundary layer heights as well atmospheric circulation patterns that promote stagnation and recirculation of air masses (Miao et al 2018;Zhao et al 2019). Dry, tropical air masses and stagnation events during the summer have led to ozone nonattainment events throughout the Midwest (Jing et al 2017) and field campaigns like the Lake Michigan Ozone Study (LMOS) and the Ozone Water-Land Environmental Transition Study (OWLETS) have highlighted how nonattainment along coastal areas can be driven by lakeand sea-breeze circulations that bring ozone-rich air inland from shallow pollution rich layers over the water (Abdi-Oskouei et al 2019;Dye et al 1995;Sullivan et al 2019).…”
Section: Public Health and Air Qualitymentioning
confidence: 99%
“…Studies have shown there is a correlation between elevated PM 2.5 pollution and decreasing boundary layer heights as well atmospheric circulation patterns that promote stagnation and recirculation of air masses (Miao et al 2018;Zhao et al 2019). Dry, tropical air masses and stagnation events during the summer have led to ozone nonattainment events throughout the Midwest (Jing et al 2017) and field campaigns like the Lake Michigan Ozone Study (LMOS) and the Ozone Water-Land Environmental Transition Study (OWLETS) have highlighted how nonattainment along coastal areas can be driven by lakeand sea-breeze circulations that bring ozone-rich air inland from shallow pollution rich layers over the water (Abdi-Oskouei et al 2019;Dye et al 1995;Sullivan et al 2019).…”
Section: Public Health and Air Qualitymentioning
confidence: 99%
“…Mastering the diffusion and transport laws of pollutants is very important to quantify air pollution levels, meteorological conditions play an important role in the diffusion and transport of pollutants (Li et al, 2012;Mao et al, 2020;Miao et al, 2017;Wang et al, 2016;Zong et al, 2021;Zhao et al, 2019Zhao et al, , 2021aZhao et al, , 2021bSun et al, 2018Sun et al, , 2019. The meteorological conditions mainly include large-scale synoptic circulation and the mesoscale meteorological conditions (Zhou et al, 2018(Zhou et al, , 2019Wang et al, 2022;Russo et al, 2014, Russo et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The meteorological conditions mainly include large-scale synoptic circulation and the mesoscale meteorological conditions (Zhou et al, 2018(Zhou et al, , 2019Wang et al, 2022;Russo et al, 2014, Russo et al, 2016. Large-scale synoptic circulation determines the specific climatic background of the study area and provides the basic dynamic field for the diffusion and transport of particulate matter (Zhao et al, 2019;Bei et al, 2022;Yan et al, 2022;Gong et al, 2022a, Gong et al, 2022b. Several studies have revealed the relationship between large-scale circulation and particulate pollution (Zhang et al, 2012, Zhang et al, 2012Zhan et al, 2019;Shu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al (2019) found that air quality is closely related to the synoptic circulation and local wind field affecting a specific area, and conducted a validation analysis in Shanghai, China. They found that the Shanghai area is most prone to severe haze under specific circulation patterns (CT1, CT2, and CT4), mainly related to cold air activity and the displacement of the high pressure system relative to Shanghai (Zhao et al, 2019). At present, there are few studies in arid and semi-arid regions dominated by dust pollution, and in China it is mainly concentrated in the northwest regions (Haijun et al, 2020;Rupakheti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%